2003
DOI: 10.4028/www.scientific.net/msf.433-436.145
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Vapor Deposition of n-Type SiC Epitaxial Layers Using Phosphine and Nitrogen as the Precursors

Abstract: Epitaxial growth of n-type SiC was carried out using PH 3 and N 2 as the dopant precursors in a chemical vapor deposition system. Compared to nitrogen, phosphorous incorporation has a weaker dependence on the flow rate and has a limited site competition effect. Also, phosphorus incorporation for a given precursor flow decreases with temperature while that of nitrogen increases. It was also observed that phosphorous incorporation increases with decreasing C/Si when the ratio is between 0.8 and 3, which suggests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
1

Year Published

2004
2004
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 9 publications
0
10
1
Order By: Relevance
“…On the other hand, opposite temperature dependence for N incorporation has also been reported. 3,4,6 Concerning the lattice polarity, the carbon-face ͑C-face͒ epitaxial layer did not show site-competition behavior, in contrast to the silicon-face ͑Si-face͒ epitaxial layer. 3,10 However, we demonstrated that the C-face also exhibited site-competition behavior under the low-pressure growth condition.…”
contrasting
confidence: 50%
See 1 more Smart Citation
“…On the other hand, opposite temperature dependence for N incorporation has also been reported. 3,4,6 Concerning the lattice polarity, the carbon-face ͑C-face͒ epitaxial layer did not show site-competition behavior, in contrast to the silicon-face ͑Si-face͒ epitaxial layer. 3,10 However, we demonstrated that the C-face also exhibited site-competition behavior under the low-pressure growth condition.…”
contrasting
confidence: 50%
“…In addition, several groups have investigated the incorporation mechanism of N using both experimental and simulative methodologies. [2][3][4][5][6][7][8][9] Different results have been reported in some of these studies. For example, Both Yamamoto et al 2 and Zhang et al 5 have reported that N incorporation decreased with increasing growth temperature.…”
mentioning
confidence: 81%
“…For example, it was reported that N incorporation decreases with increasing growth temperature based on cold-wall chemical vapor deposition (CVD) [1]. On the other hand, the opposite temperature dependence of N doping was also observed when hot-wall CVD was used [2,3,5]. Concerning the lattice polarity, the carbon-face (C-face) has not shown the site-competition behavior exhibited by the silicon-face (Si-face) [2,10].…”
Section: Introductionmentioning
confidence: 92%
“…Several groups have well investigated the doping mechanism of N and Al using both experimental and simulative methodologies [1][2][3][4][5][6][7][8][9]. However, it is not enough to completely understand the mechanism of impurity incorporation into SiC.…”
Section: Introductionmentioning
confidence: 98%
“…49,50 P incorporation in high amounts by CVD is difficult because of the low incorporation level obtained and the high toxicity of PH 3 , which is the common precursor used. 51 Introducing some P atoms in non-Al-based melts during SiC growth by VLS could bring an alternative solution to both problems of safety and incorporation level.…”
Section: Perspectivesmentioning
confidence: 99%